Novel environment-friendly flame-retardant corrugated paper and preparation method thereof

By adding nitrogen-phosphorus modified isocyanate-based polyurethane and using flame retardant adhesives containing a variety of flame retardant components during the preparation of corrugated paper, the problem of insufficient flame retardant performance of traditional corrugated paper is solved, and efficient flame retardant effect and good mechanical properties are achieved.

CN119910984APending Publication Date: 2025-05-02XUZHOU XINWEI BIOTECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510188665.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The flame retardant performance of traditional corrugated paper is insufficient and cannot meet the market's demand for versatility.

Method used

During the preparation of corrugated paper, nitrogen-phosphorus modified isocyanate-based polyurethane is added, and flame retardant adhesives containing oxidized tapioca starch, phosphate-esterified urea formaldehyde resin, nitrogen-phosphorus modified isocyanate-based polyurethane and nano aluminum hydroxide are used to form environmentally friendly flame retardant corrugated paper by bonding the upper paper, V-shaped flame retardant core base layer and the lower paper.

Benefits of technology

It significantly improves the flame retardant performance of corrugated paper, extends the burn-up time of vertical combustion, reduces the limit oxygen index, enhances the chemical stability and high temperature stability of the material, and maintains good mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses novel environment-friendly flame-retardant corrugated paper and a preparation method thereof, and belongs to the technical field of paperboard products. The corrugated paper is formed by bonding upper surface paper, a V-shaped flame-retardant core base layer and lower surface paper through a flame-retardant adhesive; the flame-retardant adhesive is prepared from the following components in parts by weight: 50 to 65 parts of oxidized cassava starch, 12 to 23 parts of phosphate esterified urea-formaldehyde resin, 5 to 15 parts of nitrogen-phosphorus modified isocyanate-based polyurethane and 2 to 8 parts of nano aluminum hydroxide; wherein the nitrogen and phosphorus modified isocyanate-based polyurethane is prepared by carrying out a reaction on isophorone isocyanate, bisphenol A type monophenyl phosphonate and modified montmorillonite, and the modified montmorillonite is prepared by carrying out a reaction on montmorillonite and polysiloxane. The corrugated paper provided by the invention has excellent flame retardant property, and also has good chemical stability and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of paperboard products, and in particular to a novel environmentally friendly flame-retardant corrugated paper and a preparation method thereof. Background Art

[0002] Corrugated paper has the significant advantages of light weight and low cost. Its light weight is not only convenient for handling and transportation, but also reduces logistics costs; its low production cost makes it an ideal choice for large-scale packaging applications. In terms of mechanical properties, corrugated paper has a certain strength and good cushioning performance. By rationally designing the shape, size and material of the corrugated paper, the compressive strength, bursting strength and other indicators of the corrugated paper can be adjusted so that it can withstand different degrees of pressure and impact. At the same time, its cushioning performance can effectively reduce the damage to items caused by vibration, collision, etc. during transportation. However, traditional corrugated paper also has some shortcomings, such as poor flame retardant properties and easy burning when exposed to open flames, which poses a major hidden danger in some application scenarios with high fire safety requirements; in addition, its water resistance needs to be improved. It is easy to absorb water and soften in a humid environment, resulting in a decrease in strength.

[0003] In the prior art, patent CN118880666B discloses an environmentally friendly mildew-proof and antibacterial corrugated paperboard and its preparation method, which improves the antibacterial and mildew-proof properties of corrugated paperboard by adding modified terminal isocyanate polyurethane to the adhesive, providing a new direction for improving the performance of corrugated paperboard. However, the patent does not test the flame retardant ability of corrugated paperboard. From the perspective of practical application, this makes the invention limited in scenarios where flame retardant properties are required, and cannot meet the market demand for the versatility of corrugated paperboard. Summary of the invention

[0004] The invention provides a novel environmentally friendly flame-retardant corrugated paper, which improves the flame-retardant performance of the corrugated paper by adding nitrogen-phosphorus modified isocyanate-based polyurethane during the preparation of the corrugated paper, thereby solving the technical problem of insufficient flame-retardant performance of the corrugated paper in the prior art.

[0005] The invention discloses a novel environmentally friendly flame-retardant corrugated paper, which is formed by bonding an upper surface paper, a V-shaped flame-retardant core base layer and a lower surface paper by a flame-retardant adhesive; The flame retardant adhesive comprises the following components in parts by weight: 50-65 parts of oxidized cassava starch, 12-23 parts of phosphated urea-formaldehyde resin, 5-15 parts of nitrogen-phosphorus modified isocyanate-based polyurethane, and 2-8 parts of nano aluminum hydroxide; Wherein, the nitrogen-phosphorus modified isocyanate-based polyurethane is prepared by reacting isophorone isocyanate, bisphenol A type monophenylphosphonate and modified montmorillonite; The modified montmorillonite is prepared by the reaction of montmorillonite and polysiloxane.

[0006] Preferably, the preparation method of the nitrogen-phosphorus modified isocyanate-based polyurethane is: S1. Preparation of bisphenol A monophenylphosphonate: Under nitrogen protection, 90-110 parts of bisphenol A, 60-70 parts of phenylphosphonyl dichloride, and 1180-220 parts of toluene are mixed, 4-6 parts of triethylamine are added, and the mixture is reacted at 75-95° C. for 4-6 hours, and diluted hydrochloric acid is added to neutralize the mixture to a pH of 7, and the mixture is filtered, washed with toluene for 2-4 times, and vacuum dried at 55-65° C. for 10-14 hours to obtain a white solid, which is bisphenol A monophenylphosphonate; S2, 45-55 parts of isophorone diisocyanate and 35-45 parts of anhydrous N-methylpyrrolidone are mixed under nitrogen protection, 25-30 parts of bisphenol A monophenylphosphonate are added at 70-95° C., 0.03-0.07 parts of dibutyltin dilaurate are added, and the reaction is carried out for 1.5-2.5 hours to obtain a phosphorus-containing polyurethane prepolymer; S3. Mix 90-110 parts of phosphorus-containing polyurethane prepolymer and 8-12 parts of modified montmorillonite, ultrasonicate for 20-40 minutes, heat to 65-75°C, react for 1-2 hours, add 3-4 parts of methyl ethyl ketone oxime and 15-25 parts of acetone, react at 45-55°C for 0.8-1.2 hours, cool to 40°C, add 1.5-2.5 parts of triethylamine and 140-160 parts of deionized water, stir at a rate of 2800-3200rpm for 25-35 minutes, and obtain nitrogen-phosphorus modified isocyanate polyurethane after reduced pressure distillation.

[0007] It can be understood that in the embodiments of the present application, the two phenolic hydroxyl groups on bisphenol A react with phenylphosphonyl dichloride under the catalysis of triethylamine to undergo a nucleophilic substitution reaction to generate bisphenol A type monophenylphosphonate, wherein the hydroxyl group of bisphenol A and the acyl chloride group of phenylphosphonyl dichloride combine to form an ester group.

[0008] Isophorone diisocyanate and bisphenol A monophenylphosphonate undergo nucleophilic addition under the catalytic action of dibutyltin dilaurate, wherein the phenolic hydroxyl group in the bisphenol A monophenylphosphonate molecule undergoes addition reaction with the isocyanate group of isophorone diisocyanate.

[0009] Polar groups such as carbamate bonds in phosphorus-containing polyurethane prepolymers are hydrogen-bonded with hydroxyl groups on the surface of modified montmorillonite. Under ultrasonic conditions, modified montmorillonite will disperse on the surface of phosphorus-containing polyurethane prepolymers to accelerate the reaction rate. The phosphorus element in the product nitrogen-phosphorus modified isocyanate polyurethane has excellent flame retardant effect, can capture free radicals during combustion and convert into stable phosphorus-containing compounds. When phosphorus-containing compounds burn, they will also generate non-flammable carbon dioxide and water, thereby diluting the concentration of combustible gases to achieve the purpose of flame retardancy. Phosphorus can also promote the dehydration and carbonization of corrugated paper surface materials at high temperatures, thereby effectively isolating heat and oxygen transmission and inhibiting the combustion reaction. The benzene ring in its structure has a unique large π bond conjugated system and a large steric hindrance, which can increase the chemical stability and high temperature stability of the product. The polyurethane structure has excellent flexibility and wear resistance. The montmorillonite structure in the modified montmorillonite further enhances the mechanical properties, and the phenyl, double bond, and methyl groups on the polysiloxane chain enhance the reaction stability, hydrophobicity, and thermal stability.

[0010] Preferably, the preparation method of the modified montmorillonite is: A1. Mix 8-12 parts of montmorillonite and 90-110 parts of anhydrous toluene, perform ultrasonic treatment for 20-40 min under nitrogen protection, add 4-6 parts of polysiloxane, react at 105-115°C for 5-7 h, cool to 25°C, centrifuge, wash alternately with toluene and anhydrous ethanol 2-4 times, and vacuum dry at 70-90°C for 10-14 hours to obtain intermediate 1; A2, 95-105 parts of anhydrous N, N-dimethylformamide and 7-8 parts of cyanuric chloride were mixed, 2.5-3.5 parts of sodium carbonate and 45-55 parts of deionized water were added under ice bath conditions, stirred for 20-40 minutes, 4-6 parts of sodium alginate were added, reacted at 20-30°C for 3-5 hours, heated to 55-65°C, reacted for 1.5-2.5 hours, cooled, precipitated with acetone, washed 2-4 times, and vacuum dried at 45-55°C for 18-30 hours to obtain intermediate 2; A3. Mix 4-6 parts of intermediate 1, 2-4 parts of intermediate 2 and 900-110 parts of anhydrous N,N-dimethylformamide, ultrasonicate for 20-40 minutes, add 0.4-0.6 parts of triethylamine, react at 65-75°C for 7-9 hours under nitrogen protection, cool to 25°C, centrifuge, wash alternately with anhydrous N,N-dimethylformamide and acetone 2-4 times, and vacuum dry at 55-65°C for 18-30 hours to obtain modified montmorillonite.

[0011] It can be understood that in the embodiments of the present application, the silanol groups on the surface of montmorillonite react with the hydroxyl groups on the surface of polysiloxane to form silicon-oxygen-silicon bonds, thereby grafting the polysiloxane onto the surface of montmorillonite.

[0012] Under low temperature alkaline conditions, cyanuric chloride undergoes a nucleophilic substitution reaction in deionized water to generate dichlorotriazinol. The chlorine atom in the dichlorotriazinol molecule undergoes a nucleophilic substitution reaction with the hydroxyl group of sodium alginate.

[0013] The carboxyl group of the sodium alginate structure on the surface of the intermediate 2 is combined with the amino group and hydroxyl group of the polysiloxane on the surface of the intermediate 1 through amidation reaction and esterification reaction to generate modified montmorillonite.

[0014] Preferably, the montmorillonite is sodium montmorillonite with a mesh size of 100 meshes.

[0015] Preferably, the preparation method of the novel polysiloxane is: 90-110 parts of tetraethoxysilane, 25-35 parts of methyltrimethoxysilane, 20-30 parts of vinyltrimethoxysilane, 30-40 parts of phenyltrimethoxysilane and 200-250 parts of anhydrous ethanol are mixed to form a reaction system, and the reaction system is stirred uniformly under nitrogen protection, 2-3 parts of concentrated hydrochloric acid and 35-45 parts of deionized water are mixed to form an acid solution, and the acid solution is added to the reaction system under ice bath conditions of 0-5°C, and the temperature is raised to 2 0-30℃, stir for 1.5-2.5h, add 0.5-1.0 parts of triethylamine to adjust the pH to 6.5-7.5, heat to 55-65℃, react for 5-7h, reflux at 75-80℃ for 10-14h, cool and distill under reduced pressure, dissolve the product in tetrahydrofuran, filter through 0.45μm filter membrane, wash with n-hexane 2-4 times, centrifuge and vacuum dry at 45-55℃ for 36-60h to obtain polysiloxane.

[0016] Preferably, the preparation method of the V-shaped flame retardant core base layer is: 25-35 parts of waste paper pulp, 6-8 parts of boron carbide fiber, 2-5 parts of phosphorus nitrogen modified isocyanate based polyurethane, and 10-20 parts of oxidized cassava starch are mixed, and after dehydration and molding, a V-shaped structure is formed by corrugated rollers.

[0017] Preferably, the raw materials for preparing the upper paper / lower paper include: 100 parts of lemon eucalyptus powder, 20-30 parts of oxidized cassava starch, 35-45 parts of waste paper pulp, 10-12 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 7-10 parts of expanded graphite.

[0018] Preferably, the preparation method of the upper paper / lower paper is: add 100 parts of lemon eucalyptus powder, 20-30 parts of oxidized cassava starch, 35-45 parts of waste paper pulp, 100-12 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 7-10 parts of expanded graphite into a pulping machine, add water and stir evenly to form a slurry, perform a pulping treatment, form sheets of the pulp after pulping, and hot-press at 170-210° C. to obtain the upper paper / lower paper.

[0019] Preferably, the preparation method of the phosphonated urea-formaldehyde resin is: B1. Mix 100-140 parts of a formaldehyde solution with a mass fraction of 35% to 40% and 80-120 parts of urea, react at 70°C for 1 hour, add 250-350 parts of diammonium phosphate and 4-6 parts of triethanolamine, heat to 80-90°C, react for 1.5-2.5 hours, and obtain a phosphated urea-formaldehyde prepolymer; B2. Mix 100 parts of phosphated urea-formaldehyde prepolymer with 20 parts of melamine at 60°C, add 0.5 parts of catalyst, heat to 90°C, react for 1.5-2h, and cool to 25°C to obtain phosphated urea-formaldehyde resin.

[0020] The present invention also discloses a method for preparing a novel environmentally friendly flame-retardant corrugated paper: the prepared flame-retardant adhesive is coated on the surface of the upper paper and the lower paper respectively, the upper paper, the V-shaped corrugated core base and the lower paper are pressed and bonded in sequence, and the paper is dried at room temperature to obtain the environmentally friendly flame-retardant corrugated paper; Wherein, the coating amount of the adhesive is 23-27g / m 2 .

[0021] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The present invention uses bisphenol A and phenylphosphonyl dichloride to synthesize bisphenol A type monophenylphosphonate, wherein two phenolic hydroxyl groups on bisphenol A react with phenylphosphonyl dichloride under the catalysis of triethylamine to undergo nucleophilic substitution reaction to generate bisphenol A type monophenylphosphonate, wherein the hydroxyl group of bisphenol A and the acyl chloride group of phenylphosphonyl dichloride combine to form an ester group.

[0022] (2) The present invention uses isophorone diisocyanate and bisphenol A type monophenylphosphonate to synthesize a phosphorus-containing polyurethane prepolymer, wherein isophorone diisocyanate and bisphenol A type monophenylphosphonate undergo nucleophilic addition under the catalytic action of dibutyltin dilaurate, wherein the phenolic hydroxyl group in the bisphenol A type monophenylphosphonate molecule undergoes addition reaction with the isocyanate group of isophorone diisocyanate.

[0023] (3) The present invention uses phosphorus-containing polyurethane prepolymer and modified montmorillonite to synthesize nitrogen-phosphorus modified isocyanate polyurethane, wherein polar groups such as urethane bonds in the phosphorus-containing polyurethane prepolymer are hydrogen-bonded with hydroxyl groups on the surface of the modified montmorillonite. Under ultrasonic conditions, the modified montmorillonite will be dispersed on the surface of the phosphorus-containing polyurethane prepolymer to accelerate the reaction rate. The phosphorus element in the product nitrogen-phosphorus modified isocyanate polyurethane has an excellent flame retardant effect, can capture free radicals during the combustion process, and convert into stable phosphorus-containing compounds. When the phosphorus-containing compounds are burned, they will also generate non-flammable carbon dioxide and water, thereby diluting the concentration of combustible gases and achieving the purpose of flame retardancy. Phosphorus can also promote the dehydration and carbonization of corrugated paper surface materials at high temperatures, thereby effectively isolating heat and oxygen transmission and inhibiting the combustion reaction. The benzene ring in its structure has a unique large π bond conjugated system and a large steric hindrance, which can increase the chemical stability and high temperature stability of the product. The polyurethane structure has excellent flexibility and wear resistance. The modified montmorillonite structure has further enhanced mechanical properties.

[0024] (4) In the process of preparing modified montmorillonite of the present invention, the silanol groups on the surface of montmorillonite react with the hydroxyl groups on the surface of polysiloxane to form silicon-oxygen-silicon bonds, thereby grafting the polysiloxane onto the surface of montmorillonite; under low temperature alkaline conditions, cyanuric chloride undergoes a nucleophilic substitution reaction in deionized water to generate dichlorotriazinol, and the chlorine atoms in the dichlorotriazinol molecules undergo a nucleophilic substitution reaction with the hydroxyl groups of sodium alginate; the carboxyl groups of the sodium alginate structure on the surface of intermediate 2 are combined with the amino groups and hydroxyl groups of the polysiloxane on the surface of intermediate 1 through amidation and esterification reactions to generate modified montmorillonite.

[0025] (5) The present invention adds phosphonated urea-formaldehyde resin and nitrogen-phosphorus modified isocyanate-based polyurethane to the flame retardant binder. The two act synergistically to greatly improve the flame retardant properties of corrugated paper, and the paper also has good mechanical properties and strong stability. DETAILED DESCRIPTION

[0026] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The tetraethoxysilane used in the embodiments of the present invention is from Shanghai Titan Technology Co., Ltd., with a purity of ≥99%; methyltrimethoxysilane is from Nanjing Shuguang Silane Chemical Co., Ltd., with a purity of ≥98%; vinyltrimethoxysilane is from Hangzhou Guibao Chemical Co., Ltd., model A-171; phenyltrimethoxysilane is from Shanghai Yuanye Biotechnology Co., Ltd., with a purity of ≥97%; 0.45 μm filter membrane is from Millipore, model mixed cellulose ester (MCE) material 0.45 μm filter membrane; montmorillonite is from Zhejiang Fenghong New Materials Co., Ltd., model sodium montmorillonite (high purity); cyanuric chloride is from Shandong Kaisheng New Materials Co., Ltd., with a purity of ≥99%; Sodium alginate comes from Qingdao Mingyue Seaweed Group Co., Ltd.; bisphenol A comes from Beijing Sinopec Mitsubishi Chemical Polycarbonate Co., Ltd.; phenylphosphonic acid dichloride comes from Bailingwei Technology Co., Ltd., with a purity of ≥98%; dibutyltin dilaurate comes from Tianjin Komeo Chemical Reagent Co., Ltd.; methyl ethyl ketone oxime comes from Jiangsu Sanmu Group Co., Ltd., with a purity of ≥99%; boron carbide fiber comes from Xi'an Chaoma Technology Co., Ltd., and the model is high-performance boron carbide fiber; oxidized cassava starch comes from Guangxi Mingyang Biochemical Technology Co., Ltd.; expanded graphite comes from Qingdao Huatai Lubrication and Sealing Technology Co., Ltd., with a mesh size of 80 mesh; nano aluminum hydroxide comes from Shandong Aluminum Co., Ltd., with a particle size of 50-100nm.

[0028] Example 1 This embodiment discloses a method for preparing environmentally friendly flame-retardant corrugated paper, and the specific steps are as follows: 90 parts of tetraethoxysilane, 25 parts of methyltrimethoxysilane, 20 parts of vinyltrimethoxysilane, 30 parts of phenyltrimethoxysilane and 200 parts of anhydrous ethanol are mixed to form a reaction system, and stirred evenly under nitrogen protection; 2 parts of concentrated hydrochloric acid are mixed with 35 parts of deionized water to form an acid solution, the acid solution is added to the reaction system under 0°C ice bath conditions, the temperature is raised to 20°C, stirred for 1.5 hours, 0.5 parts of triethylamine are added to adjust the pH to 6.5, the temperature is raised to 55°C, the reaction is performed for 5 hours, and the reaction is refluxed at 75°C for 10 hours; after cooling, the product is distilled under reduced pressure, dissolved in tetrahydrofuran, filtered through a 0.45μm filter membrane, washed twice with n-hexane, centrifuged, and vacuum dried at 45°C for 36 hours to obtain polysiloxane.

[0029] 8 parts of montmorillonite and 90 parts of anhydrous toluene were mixed, ultrasonicated for 20 minutes under nitrogen protection, 4 parts of polysiloxane were added, reacted at 105°C for 5 hours, cooled to 25°C, centrifuged, washed alternately with toluene and anhydrous ethanol twice, and vacuum dried at 70°C for 10 hours to obtain intermediate 1.

[0030] Mix 95 parts of anhydrous N,N-dimethylformamide and 7 parts of cyanuric chloride, add 2.5 parts of sodium carbonate and 45 parts of deionized water under ice bath conditions, stir for 20 minutes, add 4 parts of sodium alginate, react at 20°C for 3 hours, heat to 55°C, react for 1.5 hours, cool, precipitate with acetone, wash twice, and vacuum dry at 45°C for 18 hours to obtain intermediate 2.

[0031] 4 parts of intermediate 1, 2 parts of intermediate 2 and 90 parts of anhydrous N, N-dimethylformamide were mixed, ultrasonicated for 20 minutes, 0.4 parts of triethylamine were added, reacted at 65°C for 7 hours under nitrogen protection, cooled to 25°C, centrifuged and washed alternately with anhydrous N, N-dimethylformamide and acetone twice, and vacuum dried at 55°C for 18 hours to obtain modified montmorillonite.

[0032] Under nitrogen protection, 90 parts of bisphenol A, 60 parts of phenylphosphonic acid dichloride, and 180 parts of toluene were mixed, 4 parts of triethylamine were added, and the mixture was reacted at 75°C for 4 hours. Dilute hydrochloric acid was added to neutralize the mixture to a pH of 7, and the mixture was filtered, washed twice with toluene, and vacuum dried at 55°C for 10 hours to obtain bisphenol A monophenylphosphonate.

[0033] 45 parts of isophorone diisocyanate and 35 parts of anhydrous N-methylpyrrolidone were mixed under nitrogen protection, 25 parts of bisphenol A monophenylphosphonate and 0.03 parts of dibutyltin dilaurate were added at 70° C., and the mixture was reacted for 1.5 hours to obtain a phosphorus-containing polyurethane prepolymer.

[0034] 90 parts of phosphorus-containing polyurethane prepolymer and 8 parts of modified montmorillonite were mixed, ultrasonicated for 20 minutes, heated to 65°C, reacted for 1 hour, 3 parts of methyl ethyl ketone oxime and 15 parts of acetone were added, reacted at 45°C for 0.8 hours, cooled to 40°C, 1.5 parts of triethylamine and 140 parts of deionized water were added, stirred at a rate of 2800 rpm for 25 minutes, and distilled under reduced pressure to obtain nitrogen-phosphorus modified isocyanate-based polyurethane.

[0035] 25 parts of waste paper pulp, 6 parts of boron carbide fiber, 2 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 10 parts of oxidized cassava starch are mixed, dehydrated and formed, and then pressed into a V-shaped structure by corrugated rollers to obtain a V-shaped flame-retardant core base layer.

[0036] 100 parts of lemon eucalyptus powder, 20 parts of oxidized cassava starch, 35 parts of waste paper pulp, 10 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 7 parts of expanded graphite are added into a pulper, water is added and stirred evenly to form a slurry, and a pulping treatment is performed. The pulped slurry is sheet-formed and hot-pressed at 170°C to obtain upper paper / lower paper.

[0037] Mix 100 parts of 35% formaldehyde solution and 80 parts of urea, react at 70°C for 1 hour, add 250 parts of ammonium dihydrogen phosphate and 4 parts of triethanolamine, heat to 80°C, react for 1.5 hours to obtain phosphated urea-formaldehyde prepolymer; mix 100 parts of phosphated urea-formaldehyde prepolymer with 20 parts of melamine at 60°C, add 0.5 parts of catalyst, heat to 90°C, react for 1.5 hours, and cool to 25°C to obtain phosphated urea-formaldehyde resin.

[0038] 50 parts of oxidized cassava starch, 12 parts of phosphated urea-formaldehyde resin, 5 parts of nitrogen-phosphorus modified isocyanate-based polyurethane, and 2 parts of nano aluminum hydroxide were uniformly mixed to obtain a flame retardant adhesive.

[0039] The prepared flame retardant adhesive was coated on the surface of the upper paper and the lower paper respectively, with a coating amount of 23g / m², and the upper paper, the V-shaped corrugated core base and the lower paper were pressed and bonded in sequence, and allowed to stand and dry at room temperature to obtain environmentally friendly flame retardant corrugated paper.

[0040] Example 2 This embodiment discloses a method for preparing environmentally friendly flame-retardant corrugated paper, and the specific steps are as follows: 95 parts of tetraethoxysilane, 28 parts of methyltrimethoxysilane, 23 parts of vinyltrimethoxysilane, 33 parts of phenyltrimethoxysilane and 210 parts of anhydrous ethanol are mixed to form a reaction system, and stirred evenly under nitrogen protection; 2.2 parts of concentrated hydrochloric acid are mixed with 38 parts of deionized water to form an acid solution, the acid solution is added to the reaction system under a 2°C ice bath condition, the temperature is raised to 22°C, stirred for 1.8 hours, 0.6 parts of triethylamine are added to adjust the pH to 6.8, the temperature is raised to 58°C, the reaction is carried out for 5.5 hours, and the reaction is refluxed at 76°C for 11 hours; after cooling, the product is distilled under reduced pressure, dissolved in tetrahydrofuran, filtered through a 0.45μm filter membrane, washed with n-hexane 3 times, centrifuged, and vacuum dried at 48°C for 40 hours to obtain polysiloxane.

[0041] 9 parts of montmorillonite and 95 parts of anhydrous toluene were mixed, ultrasonicated for 25 minutes under nitrogen protection, 4.5 parts of polysiloxane were added, reacted at 108°C for 5.5 hours, cooled to 25°C, centrifuged, washed alternately with toluene and anhydrous ethanol for 3 times, and vacuum dried at 75°C for 11 hours to obtain intermediate 1.

[0042] Mix 98 parts of anhydrous N,N-dimethylformamide and 7.2 parts of cyanuric chloride, add 2.8 parts of sodium carbonate and 48 parts of deionized water under ice bath conditions, stir for 25 minutes, add 4.5 parts of sodium alginate, react at 22°C for 3.5 hours, heat to 58°C, react for 1.8 hours, cool, precipitate with acetone, wash three times, and dry in vacuum at 48°C for 20 hours to obtain intermediate 2.

[0043] 4.5 parts of intermediate 1, 2.5 parts of intermediate 2 and 95 parts of anhydrous N, N-dimethylformamide were mixed, ultrasonicated for 25 minutes, 0.45 parts of triethylamine were added, reacted at 68°C for 7.5 hours under nitrogen protection, cooled to 25°C, centrifuged and washed alternately with anhydrous N, N-dimethylformamide and acetone for 3 times, and vacuum dried at 58°C for 20 hours to obtain modified montmorillonite.

[0044] Under nitrogen protection, 95 parts of bisphenol A, 62 parts of phenylphosphonic acid dichloride, and 190 parts of toluene were mixed, 4.5 parts of triethylamine were added, and the mixture was reacted at 78°C for 4.5 hours. Dilute hydrochloric acid was added to neutralize the mixture to a pH of 7, and the mixture was filtered, washed with toluene for 3 times, and vacuum dried at 58°C for 11 hours to obtain bisphenol A monophenylphosphonate.

[0045] 48 parts of isophorone diisocyanate and 38 parts of anhydrous N-methylpyrrolidone were mixed under nitrogen protection, 26 parts of bisphenol A monophenylphosphonate and 0.04 parts of dibutyltin dilaurate were added at 75° C., and the mixture was reacted for 1.8 hours to obtain a phosphorus-containing polyurethane prepolymer.

[0046] 95 parts of phosphorus-containing polyurethane prepolymer and 9 parts of modified montmorillonite were mixed, ultrasonicated for 25 minutes, heated to 68°C, reacted for 1.2 hours, 3.2 parts of methyl ethyl ketone oxime and 18 parts of acetone were added, reacted at 48°C for 0.9 hours, cooled to 40°C, 1.8 parts of triethylamine and 145 parts of deionized water were added, stirred at a rate of 2900 rpm for 28 minutes, and distilled under reduced pressure to obtain nitrogen-phosphorus modified isocyanate-based polyurethane.

[0047] 28 parts of waste paper pulp, 6.5 parts of boron carbide fiber, 2.5 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 12 parts of oxidized cassava starch were mixed, dehydrated and formed, and then pressed into a V-shaped structure by corrugated rollers to obtain a V-shaped flame-retardant core base layer.

[0048] 100 parts of lemon eucalyptus powder, 22 parts of oxidized cassava starch, 38 parts of waste paper pulp, 10.5 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 7.5 parts of expanded graphite are added into a pulper, and water is added and stirred to form a slurry, which is then pulped. The pulp is sheeted and hot-pressed at 180°C to obtain upper paper / lower paper.

[0049] Mix 110 parts of 36% formaldehyde solution and 90 parts of urea, react at 70°C for 1 hour, add 280 parts of ammonium dihydrogen phosphate and 4.5 parts of triethanolamine, heat to 82°C, react for 1.8 hours to obtain phosphated urea-formaldehyde prepolymer; mix 100 parts of phosphated urea-formaldehyde prepolymer with 20 parts of melamine at 60°C, add 0.5 parts of catalyst, heat to 90°C, react for 1.6 hours, and cool to 25°C to obtain phosphated urea-formaldehyde resin.

[0050] 52 parts of oxidized cassava starch, 14 parts of phosphated urea-formaldehyde resin, 7 parts of nitrogen-phosphorus modified isocyanate-based polyurethane, and 3 parts of nano aluminum hydroxide were uniformly mixed to obtain a flame retardant adhesive.

[0051] The prepared flame retardant adhesive was coated on the surface of the upper paper and the lower paper respectively, with a coating amount of 24g / m², and the upper paper, the V-shaped corrugated core base and the lower paper were pressed and bonded in sequence, and allowed to stand and dry at room temperature to obtain environmentally friendly flame retardant corrugated paper.

[0052] Example 3 This embodiment discloses a method for preparing environmentally friendly flame-retardant corrugated paper, and the specific steps are as follows: 100 parts of tetraethoxysilane, 30 parts of methyltrimethoxysilane, 25 parts of vinyltrimethoxysilane, 35 parts of phenyltrimethoxysilane and 225 parts of anhydrous ethanol are mixed to form a reaction system, and stirred evenly under nitrogen protection; 2.5 parts of concentrated hydrochloric acid are mixed with 40 parts of deionized water to form an acid solution, the acid solution is added to the reaction system under a 3°C ice bath condition, the temperature is raised to 25°C, stirred for 2 hours, 0.7 parts of triethylamine are added to adjust the pH to 7, the temperature is raised to 60°C, the reaction is carried out for 6 hours, and the reaction is refluxed at 78°C for 12 hours; after cooling, the product is distilled under reduced pressure, dissolved in tetrahydrofuran, filtered through a 0.45μm filter membrane, washed with n-hexane 3 times, centrifuged, and vacuum dried at 50°C for 48 hours to obtain polysiloxane.

[0053] 10 parts of montmorillonite and 100 parts of anhydrous toluene were mixed, ultrasonicated for 30 minutes under nitrogen protection, 5 parts of polysiloxane were added, reacted at 110°C for 6 hours, cooled to 25°C, centrifuged, washed alternately with toluene and anhydrous ethanol for 3 times, and vacuum dried at 80°C for 12 hours to obtain intermediate 1.

[0054] Mix 100 parts of anhydrous N,N-dimethylformamide and 7.5 parts of cyanuric chloride, add 3 parts of sodium carbonate and 50 parts of deionized water in an ice bath, stir for 30 minutes, add 5 parts of sodium alginate, react at 25°C for 4 hours, heat to 60°C, react for 2 hours, cool, precipitate with acetone, wash 3 times, and dry in vacuum at 50°C for 24 hours to obtain intermediate 2.

[0055] Mix 5 parts of intermediate 1, 3 parts of intermediate 2 and 100 parts of anhydrous N, N-dimethylformamide, ultrasonicate for 30 minutes, add 0.5 parts of triethylamine, react at 70°C for 8 hours under nitrogen protection, cool to 25°C, centrifuge, wash alternately with anhydrous N, N-dimethylformamide and acetone for 3 times, and vacuum dry at 60°C for 24 hours to obtain modified montmorillonite.

[0056] Under nitrogen protection, 100 parts of bisphenol A, 65 parts of phenylphosphonic acid dichloride, and 200 parts of toluene were mixed, 5 parts of triethylamine were added, and the mixture was reacted at 85°C for 5 hours. Dilute hydrochloric acid was added to neutralize the mixture to a pH of 7, and the mixture was filtered, washed with toluene for 3 times, and vacuum dried at 60°C for 12 hours to obtain bisphenol A monophenylphosphonate.

[0057] 50 parts of isophorone diisocyanate and 40 parts of anhydrous N-methylpyrrolidone were mixed under nitrogen protection, 28 parts of bisphenol A type monophenylphosphonate and 0.05 parts of dibutyltin dilaurate were added at 80° C. and reacted for 2 hours to obtain a phosphorus-containing polyurethane prepolymer.

[0058] 100 parts of phosphorus-containing polyurethane prepolymer and 10 parts of modified montmorillonite were mixed, ultrasonicated for 30 minutes, heated to 70°C, reacted for 1.5 hours, 3.5 parts of methyl ethyl ketone oxime and 20 parts of acetone were added, reacted at 50°C for 1 hour, cooled to 40°C, 2 parts of triethylamine and 150 parts of deionized water were added, stirred at 3000 rpm for 30 minutes, and distilled under reduced pressure to obtain nitrogen-phosphorus modified isocyanate-based polyurethane.

[0059] 30 parts of waste paper pulp, 7 parts of boron carbide fiber, 3 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 15 parts of oxidized cassava starch are mixed, dehydrated and formed, and then pressed into a V-shaped structure by corrugated rollers to obtain a V-shaped flame-retardant core base layer.

[0060] 100 parts of lemon eucalyptus powder, 25 parts of oxidized cassava starch, 40 parts of waste paper pulp, 11 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 8 parts of expanded graphite are added into a pulper, water is added and stirred evenly to form a slurry, and a pulping treatment is performed. The pulped slurry is sheet-formed and hot-pressed at 190°C to obtain upper paper / lower paper.

[0061] Mix 120 parts of 37% formaldehyde solution and 100 parts of urea, react at 70°C for 1 hour, add 300 parts of ammonium dihydrogen phosphate and 5 parts of triethanolamine, heat to 85°C, react for 2 hours to obtain phosphated urea-formaldehyde prepolymer; mix 100 parts of phosphated urea-formaldehyde prepolymer with 20 parts of melamine at 60°C, add 0.5 parts of catalyst, heat to 90°C, react for 1.7 hours, and cool to 25°C to obtain phosphated urea-formaldehyde resin.

[0062] 55 parts of oxidized cassava starch, 17 parts of phosphated urea-formaldehyde resin, 10 parts of nitrogen-phosphorus modified isocyanate-based polyurethane, and 5 parts of nano aluminum hydroxide were uniformly mixed to obtain a flame retardant adhesive.

[0063] The prepared flame retardant adhesive was coated on the surface of the upper paper and the lower paper respectively, with a coating amount of 25g / m², and the upper paper, the V-shaped corrugated core base and the lower paper were pressed and bonded in sequence, and allowed to stand and dry at room temperature to obtain environmentally friendly flame retardant corrugated paper.

[0064] Example 4 This embodiment discloses a method for preparing environmentally friendly flame-retardant corrugated paper, and the specific steps are as follows: 105 parts of tetraethoxysilane, 32 parts of methyltrimethoxysilane, 27 parts of vinyltrimethoxysilane, 37 parts of phenyltrimethoxysilane and 235 parts of anhydrous ethanol are mixed to form a reaction system, and stirred evenly under nitrogen protection; 2.8 parts of concentrated hydrochloric acid are mixed with 42 parts of deionized water to form an acid solution, the acid solution is added to the reaction system under a 4°C ice bath condition, the temperature is raised to 28°C, stirred for 2.2 hours, 0.8 parts of triethylamine are added to adjust the pH to 7.2, the temperature is raised to 62°C, the reaction is carried out for 6.5 hours, and the reaction is refluxed at 79°C for 13 hours; after cooling, the product is distilled under reduced pressure, dissolved in tetrahydrofuran, filtered through a 0.45μm filter membrane, washed with n-hexane 4 times, centrifuged, and vacuum dried at 52°C for 52 hours to obtain polysiloxane.

[0065] 11 parts of montmorillonite and 105 parts of anhydrous toluene were mixed, ultrasonicated for 35 minutes under nitrogen protection, 5.5 parts of polysiloxane were added, reacted at 112°C for 6.5 hours, cooled to 25°C, centrifuged, washed alternately with toluene and anhydrous ethanol for 4 times, and vacuum dried at 85°C for 13 hours to obtain intermediate 1.

[0066] Mix 103 parts of anhydrous N,N-dimethylformamide and 7.8 parts of cyanuric chloride, add 3.2 parts of sodium carbonate and 52 parts of deionized water in an ice bath, stir for 35 minutes, add 5.5 parts of sodium alginate, react at 27°C for 4.5 hours, heat to 62°C, react for 2.2 hours, cool, precipitate with acetone, wash 4 times, and dry in vacuum at 52°C for 26 hours to obtain intermediate 2.

[0067] 5.5 parts of intermediate 1, 3.5 parts of intermediate 2 and 105 parts of anhydrous N, N-dimethylformamide were mixed, ultrasonicated for 35 minutes, 0.55 parts of triethylamine were added, reacted at 72°C for 8.5 hours under nitrogen protection, cooled to 25°C, centrifuged, washed alternately with anhydrous N, N-dimethylformamide and acetone for 4 times, and vacuum dried at 62°C for 26 hours to obtain modified montmorillonite.

[0068] Under nitrogen protection, 105 parts of bisphenol A, 67 parts of phenylphosphonic acid dichloride, and 210 parts of toluene were mixed, 5.5 parts of triethylamine were added, and the mixture was reacted at 90°C for 5.5 hours. Dilute hydrochloric acid was added to neutralize the mixture to a pH of 7, and the mixture was filtered, washed with toluene for 4 times, and vacuum dried at 62°C for 13 hours to obtain bisphenol A monophenylphosphonate.

[0069] 52 parts of isophorone diisocyanate and 42 parts of anhydrous N-methylpyrrolidone were mixed under nitrogen protection, 29 parts of bisphenol A monophenylphosphonate and 0.06 parts of dibutyltin dilaurate were added at 85° C., and the mixture was reacted for 2.2 hours to obtain a phosphorus-containing polyurethane prepolymer.

[0070] 105 parts of phosphorus-containing polyurethane prepolymer and 11 parts of modified montmorillonite were mixed, ultrasonicated for 35 minutes, heated to 72°C, reacted for 1.8 hours, 3.8 parts of methyl ethyl ketone oxime and 22 parts of acetone were added, reacted at 52°C for 1.1 hours, cooled to 40°C, 2.2 parts of triethylamine and 155 parts of deionized water were added, stirred at a rate of 3100 rpm for 32 minutes, and distilled under reduced pressure to obtain nitrogen-phosphorus modified isocyanate-based polyurethane.

[0071] 32 parts of waste paper pulp, 7.5 parts of boron carbide fiber, 4 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 18 parts of oxidized cassava starch were mixed, dehydrated and formed, and then pressed into a V-shaped structure by corrugated rollers to obtain a V-shaped flame-retardant core base layer.

[0072] 100 parts of lemon eucalyptus powder, 28 parts of oxidized cassava starch, 42 parts of waste paper pulp, 11.5 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 9 parts of expanded graphite are added into a pulper, water is added and stirred evenly to form a slurry, which is then pulped, and the pulp is sheeted and formed, which is hot-pressed at 200°C to obtain upper paper / lower paper.

[0073] Mix 130 parts of 38% formaldehyde solution and 110 parts of urea, react at 70°C for 1 hour, add 320 parts of ammonium dihydrogen phosphate and 5.5 parts of triethanolamine, heat to 88°C, react for 2.2 hours to obtain phosphated urea-formaldehyde prepolymer; mix 100 parts of phosphated urea-formaldehyde prepolymer with 20 parts of melamine at 60°C, add 0.5 parts of catalyst, heat to 90°C, react for 1.8 hours, and cool to 25°C to obtain phosphated urea-formaldehyde resin.

[0074] 60 parts of oxidized cassava starch, 20 parts of phosphated urea-formaldehyde resin, 12 parts of nitrogen-phosphorus modified isocyanate-based polyurethane, and 6 parts of nano aluminum hydroxide were uniformly mixed to obtain a flame retardant adhesive.

[0075] The prepared flame retardant adhesive was coated on the surface of the upper paper and the lower paper respectively, with a coating amount of 26g / m², and the upper paper, the V-shaped corrugated core base and the lower paper were pressed and bonded in sequence, and allowed to stand and dry at room temperature to obtain environmentally friendly flame retardant corrugated paper.

[0076] Example 5 This embodiment discloses a method for preparing environmentally friendly flame-retardant corrugated paper, and the specific steps are as follows: 110 parts of tetraethoxysilane, 35 parts of methyltrimethoxysilane, 30 parts of vinyltrimethoxysilane, 40 parts of phenyltrimethoxysilane and 250 parts of anhydrous ethanol are mixed to form a reaction system, and stirred evenly under nitrogen protection; 3 parts of concentrated hydrochloric acid are mixed with 45 parts of deionized water to form an acid solution, the acid solution is added to the reaction system under 5°C ice bath conditions, the temperature is raised to 30°C, stirred for 2.5 hours, 1.0 part of triethylamine is added to adjust the pH to 7.5, the temperature is raised to 65°C, the reaction is carried out for 7 hours, and the reaction is refluxed at 80°C for 14 hours; after cooling, the product is distilled under reduced pressure, dissolved in tetrahydrofuran, filtered through a 0.45μm filter membrane, washed with n-hexane 4 times, centrifuged, and vacuum dried at 55°C for 60 hours to obtain polysiloxane.

[0077] 12 parts of montmorillonite and 110 parts of anhydrous toluene were mixed, ultrasonicated for 40 minutes under nitrogen protection, 6 parts of polysiloxane were added, reacted at 115°C for 7 hours, cooled to 25°C, centrifuged, washed alternately with toluene and anhydrous ethanol for 4 times, and vacuum dried at 90°C for 14 hours to obtain intermediate 1.

[0078] Mix 105 parts of anhydrous N,N-dimethylformamide and 8 parts of cyanuric chloride, add 3.5 parts of sodium carbonate and 55 parts of deionized water under ice bath conditions, stir for 40 minutes, add 6 parts of sodium alginate, react at 30°C for 5 hours, heat to 65°C, react for 2.5 hours, cool, precipitate with acetone, wash 4 times, and vacuum dry at 55°C for 30 hours to obtain intermediate 2.

[0079] 6 parts of intermediate 1, 4 parts of intermediate 2 and 110 parts of anhydrous N, N-dimethylformamide were mixed, ultrasonicated for 40 minutes, 0.6 parts of triethylamine were added, reacted at 75°C for 9 hours under nitrogen protection, cooled to 25°C, centrifuged and washed alternately with anhydrous N, N-dimethylformamide and acetone for 4 times, and vacuum dried at 65°C for 30 hours to obtain modified montmorillonite.

[0080] Under nitrogen protection, 110 parts of bisphenol A, 70 parts of phenylphosphonic acid dichloride, and 220 parts of toluene were mixed, 6 parts of triethylamine were added, and the mixture was reacted at 95°C for 6 hours. Dilute hydrochloric acid was added to neutralize the mixture to a pH of 7, and the mixture was filtered, washed with toluene for 4 times, and vacuum dried at 65°C for 14 hours to obtain bisphenol A monophenylphosphonate.

[0081] 55 parts of isophorone diisocyanate and 45 parts of anhydrous N-methylpyrrolidone were mixed under nitrogen protection, 30 parts of bisphenol A monophenylphosphonate and 0.07 parts of dibutyltin dilaurate were added at 95° C., and the mixture was reacted for 2.5 hours to obtain a phosphorus-containing polyurethane prepolymer.

[0082] 110 parts of phosphorus-containing polyurethane prepolymer and 12 parts of modified montmorillonite were mixed, ultrasonicated for 40 minutes, heated to 75°C, reacted for 2 hours, 4 parts of methyl ethyl ketone oxime and 25 parts of acetone were added, reacted at 55°C for 1.2 hours, cooled to 40°C, 2.5 parts of triethylamine and 160 parts of deionized water were added, stirred at a rate of 3200 rpm for 35 minutes, and distilled under reduced pressure to obtain nitrogen-phosphorus modified isocyanate-based polyurethane.

[0083] 35 parts of waste paper pulp, 8 parts of boron carbide fiber, 5 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 20 parts of oxidized cassava starch are mixed, dehydrated and formed, and then pressed into a V-shaped structure by corrugated rollers to obtain a V-shaped flame-retardant core base layer.

[0084] 100 parts of lemon eucalyptus powder, 30 parts of oxidized cassava starch, 45 parts of waste paper pulp, 12 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 10 parts of expanded graphite are added into a pulper, water is added and stirred evenly to form a slurry, and a pulping treatment is performed. The pulped slurry is sheet-formed and hot-pressed at 210°C to obtain upper paper / lower paper.

[0085] Mix 140 parts of 40% formaldehyde solution and 120 parts of urea, react at 70°C for 1 hour, add 350 parts of ammonium dihydrogen phosphate and 6 parts of triethanolamine, heat to 90°C, react for 2.5 hours to obtain phosphated urea-formaldehyde prepolymer; mix 100 parts of phosphated urea-formaldehyde prepolymer with 20 parts of melamine at 60°C, add 0.5 parts of catalyst, heat to 90°C, react for 2 hours, and cool to 25°C to obtain phosphated urea-formaldehyde resin.

[0086] 65 parts of oxidized cassava starch, 23 parts of phosphated urea-formaldehyde resin, 15 parts of nitrogen-phosphorus modified isocyanate-based polyurethane, and 8 parts of nano aluminum hydroxide were uniformly mixed to obtain a flame retardant adhesive.

[0087] The prepared flame retardant adhesive was coated on the surface of the upper paper and the lower paper respectively, with a coating amount of 27g / m², and the upper paper, the V-shaped corrugated core base and the lower paper were pressed and bonded in sequence, and allowed to stand and dry at room temperature to obtain environmentally friendly flame retardant corrugated paper.

[0088] Comparative Example 1 The difference between this comparative example and Example 1 is that no nitrogen-phosphorus-modified isocyanate-based polyurethane is added to the flame retardant adhesive.

[0089] 50 parts of oxidized cassava starch, 12 parts of phosphated urea-formaldehyde resin and 2 parts of nano aluminum hydroxide were uniformly mixed to obtain a flame retardant adhesive.

[0090] The prepared flame retardant adhesive was coated on the surface of the upper paper and the lower paper respectively, with a coating amount of 23g / m², and the upper paper, the V-shaped corrugated core base and the lower paper were pressed and bonded in sequence, and allowed to stand and dry at room temperature to obtain environmentally friendly flame retardant corrugated paper.

[0091] Comparative Example 2 The difference between this comparative example and Example 1 is that no phosphated urea-formaldehyde resin is added.

[0092] 50 parts of oxidized cassava starch, 5 parts of nitrogen-phosphorus modified isocyanate-based polyurethane and 2 parts of nano aluminum hydroxide were mixed evenly to obtain a flame retardant adhesive.

[0093] The prepared flame retardant adhesive was coated on the surface of the upper paper and the lower paper respectively, with a coating amount of 23g / m², and the upper paper, the V-shaped corrugated core base and the lower paper were pressed and bonded in sequence, and allowed to stand and dry at room temperature to obtain environmentally friendly flame retardant corrugated paper.

[0094] Comparative Example 3 The difference between this comparative example and Example 1 is that no polysiloxane is added.

[0095] 8 parts of montmorillonite and 90 parts of anhydrous toluene were mixed, ultrasonicated for 20 minutes under nitrogen protection, reacted at 105°C for 5 hours, cooled to 25°C, centrifuged, washed alternately with toluene and anhydrous ethanol twice, and vacuum dried at 70°C for 10 hours to obtain intermediate 1.

[0096] Mix 95 parts of anhydrous N,N-dimethylformamide and 7 parts of cyanuric chloride, add 2.5 parts of sodium carbonate and 45 parts of deionized water under ice bath conditions, stir for 20 minutes, add 4 parts of sodium alginate, react at 20°C for 3 hours, heat to 55°C, react for 1.5 hours, cool, precipitate with acetone, wash twice, and vacuum dry at 45°C for 18 hours to obtain intermediate 2.

[0097] 4 parts of intermediate 1, 2 parts of intermediate 2 and 90 parts of anhydrous N, N-dimethylformamide were mixed, ultrasonicated for 20 minutes, 0.4 parts of triethylamine were added, reacted at 65°C for 7 hours under nitrogen protection, cooled to 25°C, centrifuged and washed alternately with anhydrous N, N-dimethylformamide and acetone twice, and vacuum dried at 55°C for 18 hours to obtain modified montmorillonite.

[0098] Under nitrogen protection, 90 parts of bisphenol A, 60 parts of phenylphosphonic acid dichloride, and 180 parts of toluene were mixed, 4 parts of triethylamine were added, and the mixture was reacted at 75°C for 4 hours. Dilute hydrochloric acid was added to neutralize the mixture to a pH of 7, and the mixture was filtered, washed twice with toluene, and vacuum dried at 55°C for 10 hours to obtain bisphenol A monophenylphosphonate.

[0099] 45 parts of isophorone diisocyanate and 35 parts of anhydrous N-methylpyrrolidone were mixed under nitrogen protection, 25 parts of bisphenol A monophenylphosphonate and 0.03 parts of dibutyltin dilaurate were added at 70° C., and the mixture was reacted for 1.5 hours to obtain a phosphorus-containing polyurethane prepolymer.

[0100] 90 parts of phosphorus-containing polyurethane prepolymer and 8 parts of modified montmorillonite were mixed, ultrasonicated for 20 minutes, heated to 65°C, reacted for 1 hour, 3 parts of methyl ethyl ketone oxime and 15 parts of acetone were added, reacted at 45°C for 0.8 hours, cooled to 40°C, 1.5 parts of triethylamine and 140 parts of deionized water were added, stirred at a rate of 2800 rpm for 25 minutes, and distilled under reduced pressure to obtain nitrogen-phosphorus modified isocyanate-based polyurethane.

[0101] 25 parts of waste paper pulp, 6 parts of boron carbide fiber, 2 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 10 parts of oxidized cassava starch are mixed, dehydrated and formed, and then pressed into a V-shaped structure by corrugated rollers to obtain a V-shaped flame-retardant core base layer.

[0102] 100 parts of lemon eucalyptus powder, 20 parts of oxidized cassava starch, 35 parts of waste paper pulp, 10 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 7 parts of expanded graphite are added into a pulper, water is added and stirred evenly to form a slurry, and a pulping treatment is performed. The pulped slurry is sheet-formed and hot-pressed at 170°C to obtain upper paper / lower paper.

[0103] Mix 100 parts of 35% formaldehyde solution and 80 parts of urea, react at 70°C for 1 hour, add 250 parts of ammonium dihydrogen phosphate and 4 parts of triethanolamine, heat to 80°C, react for 1.5 hours to obtain phosphated urea-formaldehyde prepolymer; mix 100 parts of phosphated urea-formaldehyde prepolymer with 20 parts of melamine at 60°C, add 0.5 parts of catalyst, heat to 90°C, react for 1.5 hours, and cool to 25°C to obtain phosphated urea-formaldehyde resin.

[0104] 50 parts of oxidized cassava starch, 12 parts of phosphated urea-formaldehyde resin, 5 parts of nitrogen-phosphorus modified isocyanate-based polyurethane, and 2 parts of nano aluminum hydroxide were uniformly mixed to obtain a flame retardant adhesive.

[0105] The prepared flame retardant adhesive was coated on the surface of the upper paper and the lower paper respectively, with a coating amount of 23g / m², and the upper paper, the V-shaped corrugated core base and the lower paper were pressed and bonded in sequence, and allowed to stand and dry at room temperature to obtain environmentally friendly flame retardant corrugated paper.

[0106] Comparative Example 4 The difference between this comparative example and Example 1 is that intermediate 2 is not added, and intermediate 1 is directly used as modified montmorillonite.

[0107] 90 parts of tetraethoxysilane, 25 parts of methyltrimethoxysilane, 20 parts of vinyltrimethoxysilane, 30 parts of phenyltrimethoxysilane and 200 parts of anhydrous ethanol are mixed to form a reaction system, and stirred evenly under nitrogen protection; 2 parts of concentrated hydrochloric acid are mixed with 35 parts of deionized water to form an acid solution, the acid solution is added to the reaction system under 0°C ice bath conditions, the temperature is raised to 20°C, stirred for 1.5 hours, 0.5 parts of triethylamine are added to adjust the pH to 6.5, the temperature is raised to 55°C, the reaction is performed for 5 hours, and the reaction is refluxed at 75°C for 10 hours; after cooling, the product is distilled under reduced pressure, dissolved in tetrahydrofuran, filtered through a 0.45μm filter membrane, washed twice with n-hexane, centrifuged, and vacuum dried at 45°C for 36 hours to obtain polysiloxane.

[0108] 8 parts of montmorillonite and 90 parts of anhydrous toluene were mixed, ultrasonicated for 20 minutes under nitrogen protection, 4 parts of polysiloxane were added, reacted at 105°C for 5 hours, cooled to 25°C, centrifuged and washed alternately with toluene and anhydrous ethanol twice, and vacuum dried at 70°C for 10 hours to obtain intermediate 1, which is modified montmorillonite.

[0109] Under nitrogen protection, 90 parts of bisphenol A, 60 parts of phenylphosphonic acid dichloride, and 180 parts of toluene were mixed, 4 parts of triethylamine were added, and the mixture was reacted at 75°C for 4 hours. Dilute hydrochloric acid was added to neutralize the mixture to a pH of 7, and the mixture was filtered, washed twice with toluene, and vacuum dried at 55°C for 10 hours to obtain bisphenol A monophenylphosphonate.

[0110] 45 parts of isophorone diisocyanate and 35 parts of anhydrous N-methylpyrrolidone were mixed under nitrogen protection, 25 parts of bisphenol A monophenylphosphonate and 0.03 parts of dibutyltin dilaurate were added at 70° C., and the mixture was reacted for 1.5 hours to obtain a phosphorus-containing polyurethane prepolymer.

[0111] 90 parts of phosphorus-containing polyurethane prepolymer and 8 parts of modified montmorillonite were mixed, ultrasonicated for 20 minutes, heated to 65°C, reacted for 1 hour, 3 parts of methyl ethyl ketone oxime and 15 parts of acetone were added, reacted at 45°C for 0.8 hours, cooled to 40°C, 1.5 parts of triethylamine and 140 parts of deionized water were added, stirred at a rate of 2800 rpm for 25 minutes, and distilled under reduced pressure to obtain nitrogen-phosphorus modified isocyanate-based polyurethane.

[0112] 25 parts of waste paper pulp, 6 parts of boron carbide fiber, 2 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 10 parts of oxidized cassava starch are mixed, dehydrated and formed, and then pressed into a V-shaped structure by corrugated rollers to obtain a V-shaped flame-retardant core base layer.

[0113] 100 parts of lemon eucalyptus powder, 20 parts of oxidized cassava starch, 35 parts of waste paper pulp, 10 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 7 parts of expanded graphite are added into a pulper, water is added and stirred evenly to form a slurry, and a pulping treatment is performed. The pulped slurry is sheet-formed and hot-pressed at 170°C to obtain upper paper / lower paper.

[0114] Mix 100 parts of 35% formaldehyde solution and 80 parts of urea, react at 70°C for 1 hour, add 250 parts of ammonium dihydrogen phosphate and 4 parts of triethanolamine, heat to 80°C, react for 1.5 hours to obtain phosphated urea-formaldehyde prepolymer; mix 100 parts of phosphated urea-formaldehyde prepolymer with 20 parts of melamine at 60°C, add 0.5 parts of catalyst, heat to 90°C, react for 1.5 hours, and cool to 25°C to obtain phosphated urea-formaldehyde resin.

[0115] 50 parts of oxidized cassava starch, 12 parts of phosphated urea-formaldehyde resin, 5 parts of nitrogen-phosphorus modified isocyanate-based polyurethane, and 2 parts of nano aluminum hydroxide were uniformly mixed to obtain a flame retardant adhesive.

[0116] The prepared flame retardant adhesive was coated on the surface of the upper paper and the lower paper respectively, with a coating amount of 23g / m², and the upper paper, the V-shaped corrugated core base and the lower paper were pressed and bonded in sequence, and allowed to stand and dry at room temperature to obtain environmentally friendly flame retardant corrugated paper.

[0117] Comparative Example 5 The difference between this comparative example and Example 1 is that, in the process of synthesizing nitrogen-phosphorus-modified isocyanate-based polyurethane, polyethylene glycol is used as a chain extender instead of modified montmorillonite.

[0118] Under nitrogen protection, 90 parts of bisphenol A, 60 parts of phenylphosphonic acid dichloride, and 180 parts of toluene were mixed, 4 parts of triethylamine were added, and the mixture was reacted at 75°C for 4 hours. Dilute hydrochloric acid was added to neutralize the mixture to a pH of 7, and the mixture was filtered, washed twice with toluene, and vacuum dried at 55°C for 10 hours to obtain bisphenol A monophenylphosphonate.

[0119] 45 parts of isophorone diisocyanate and 35 parts of anhydrous N-methylpyrrolidone were mixed under nitrogen protection, 25 parts of bisphenol A monophenylphosphonate and 0.03 parts of dibutyltin dilaurate were added at 70° C., and the mixture was reacted for 1.5 hours to obtain a phosphorus-containing polyurethane prepolymer.

[0120] 90 parts of phosphorus-containing polyurethane prepolymer and 8 parts of polyethylene glycol were mixed, ultrasonicated for 20 minutes, heated to 65°C, reacted for 1 hour, 3 parts of methyl ethyl ketone oxime and 15 parts of acetone were added, reacted at 45°C for 0.8 hours, cooled to 40°C, 1.5 parts of triethylamine and 140 parts of deionized water were added, stirred at a rate of 2800 rpm for 25 minutes, and distilled under reduced pressure to obtain nitrogen-phosphorus modified isocyanate-based polyurethane.

[0121] 25 parts of waste paper pulp, 6 parts of boron carbide fiber, 2 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 10 parts of oxidized cassava starch are mixed, dehydrated and formed, and then pressed into a V-shaped structure by corrugated rollers to obtain a V-shaped flame-retardant core base layer.

[0122] 100 parts of lemon eucalyptus powder, 20 parts of oxidized cassava starch, 35 parts of waste paper pulp, 10 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 7 parts of expanded graphite are added into a pulper, water is added and stirred evenly to form a slurry, and a pulping treatment is performed. The pulped slurry is sheet-formed and hot-pressed at 170°C to obtain upper paper / lower paper.

[0123] Mix 100 parts of 35% formaldehyde solution and 80 parts of urea, react at 70°C for 1 hour, add 250 parts of ammonium dihydrogen phosphate and 4 parts of triethanolamine, heat to 80°C, react for 1.5 hours to obtain phosphated urea-formaldehyde prepolymer; mix 100 parts of phosphated urea-formaldehyde prepolymer with 20 parts of melamine at 60°C, add 0.5 parts of catalyst, heat to 90°C, react for 1.5 hours, and cool to 25°C to obtain phosphated urea-formaldehyde resin.

[0124] 50 parts of oxidized cassava starch, 12 parts of phosphated urea-formaldehyde resin, 5 parts of nitrogen-phosphorus modified isocyanate-based polyurethane, and 2 parts of nano aluminum hydroxide were uniformly mixed to obtain a flame retardant adhesive.

[0125] The prepared flame retardant adhesive was coated on the surface of the upper paper and the lower paper respectively, with a coating amount of 23g / m², and the upper paper, the V-shaped corrugated core base and the lower paper were pressed and bonded in sequence, and allowed to stand and dry at room temperature to obtain environmentally friendly flame retardant corrugated paper.

[0126] Comparative Example 6 The difference between this comparative example and Example 1 is that no phosphated urea-formaldehyde resin and nitrogen-phosphorus modified isocyanate-based polyurethane are added.

[0127] 50 parts of oxidized cassava starch and 2 parts of nano aluminum hydroxide were uniformly mixed to obtain a flame retardant adhesive.

[0128] The prepared flame retardant adhesive was coated on the surface of the upper paper and the lower paper respectively, with a coating amount of 23g / m², and the upper paper, the V-shaped corrugated core base and the lower paper were pressed and bonded in sequence, and allowed to stand and dry at room temperature to obtain environmentally friendly flame retardant corrugated paper.

[0129] Flame retardant performance test: Use a vertical combustion tester to test the vertical combustion performance of corrugated paper according to the method of GB / T 14656-2009; use an oxygen index tester to test the limiting oxygen index of corrugated paper.

[0130] Table 1 shows the flame retardant performance test results

[0131] It can be seen from the test results in the above table that with the increase of the content of nitrogen-phosphorus modified isocyanate-based polyurethane in corrugated paper and adhesive, the afterflame time and smoldering time of vertical combustion decrease, and the limiting oxygen index increases, among which Example 5 reaches the highest. This is because the nitrogen-phosphorus modified isocyanate-based polyurethane contains phosphorus element and modified montmorillonite structure, which can enhance the flame retardant effect of corrugated paper; on the other hand, the phosphated urea-formaldehyde resin also has excellent flame retardant properties. The ammonium dihydrogen phosphate added during the synthesis process introduces phosphorus element. When the temperature rises, the phosphorus-containing compound will decompose to generate phosphoric acid, metaphosphoric acid and other substances. These acids can promote the dehydration and carbonization of organic components such as cellulose in corrugated paper, and form a dense carbon layer on the surface of the material. The carbon layer has the function of heat insulation and oxygen isolation, which can effectively prevent heat and oxygen from transferring to the inside of the material and inhibit the combustion reaction. Urea and melamine provide nitrogen elements for the system. Nitrogen elements will generate non-combustible gases such as nitrogen when burning. These gases can dilute the oxygen concentration in the combustion area, reduce the concentration of combustible gases, and make it difficult to continue combustion. Moreover, there is a synergistic flame retardant effect between nitrogen and phosphorus. When phosphorus and nitrogen exist at the same time, an expandable carbon layer will be formed at high temperature, further enhancing the flame retardant effect; the chemical bonds in phosphated urea-formaldehyde resin, such as CN, POC, etc., have high thermal stability during combustion and are not easy to break, which enables the resin to maintain structural integrity at high temperatures, enhances the protection of corrugated paper, and reduces the thermal decomposition and combustion of the material.

[0132] Comparative Example 1 does not contain nitrogen-phosphorus modified isocyanate-based polyurethane; Comparative Example 2 does not contain phosphated urea-formaldehyde resin; Comparative Example 3 does not contain polysiloxane; Comparative Example 4 does not contain intermediate 2; Comparative Example 5 does not contain modified montmorillonite; Comparative Example 6 does not contain nitrogen-phosphorus modified isocyanate-based polyurethane and phosphated urea-formaldehyde resin.

[0133] It can be seen from the data of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 6 that the nitrogen-phosphorus modified isocyanate-based polyurethane and the phosphated urea-formaldehyde resin have synergistic flame retardant properties.

[0134] Corrugated cardboard mechanical properties test: Tested in accordance with GB / T 6544-2008 standard.

[0135] Table 3 shows the test results of mechanical properties of corrugated paper

[0136] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A new type of environmentally friendly flame-retardant corrugated paper, characterized in that: It is made of upper paper, V-shaped flame-retardant core base and lower paper bonded by flame-retardant adhesive; The flame retardant adhesive comprises the following components in parts by weight: 50-65 parts of oxidized cassava starch, 12-23 parts of phosphated urea-formaldehyde resin, 5-15 parts of nitrogen-phosphorus modified isocyanate-based polyurethane, and 2-8 parts of nano aluminum hydroxide; Wherein, the nitrogen-phosphorus modified isocyanate-based polyurethane is prepared by reacting isophorone isocyanate, bisphenol A type monophenylphosphonate and modified montmorillonite; The modified montmorillonite is prepared by the reaction of montmorillonite and polysiloxane.

2. The corrugated paper according to claim 1, characterized in that: The preparation method of the nitrogen-phosphorus modified isocyanate-based polyurethane is as follows: S1. Preparation of bisphenol A monophenylphosphonate: Under nitrogen protection, 90-110 parts of bisphenol A, 60-70 parts of phenylphosphonyl dichloride, and 1180-220 parts of toluene are mixed, 4-6 parts of triethylamine are added, and the mixture is reacted at 75-95° C. for 4-6 hours, and diluted hydrochloric acid is added to neutralize the mixture to a pH of 7, and the mixture is filtered, washed with toluene for 2-4 times, and vacuum dried at 55-65° C. for 10-14 hours to obtain a white solid, which is bisphenol A monophenylphosphonate; S2, 45-55 parts of isophorone diisocyanate and 35-45 parts of anhydrous N-methylpyrrolidone are mixed under nitrogen protection, 25-30 parts of bisphenol A monophenylphosphonate are added at 70-95° C., 0.03-0.07 parts of dibutyltin dilaurate are added, and the reaction is carried out for 1.5-2.5 hours to obtain a phosphorus-containing polyurethane prepolymer; S3. Mix 90-110 parts of phosphorus-containing polyurethane prepolymer and 8-12 parts of modified montmorillonite, ultrasonicate for 20-40 minutes, heat to 65-75°C, react for 1-2 hours, add 3-4 parts of methyl ethyl ketone oxime and 15-25 parts of acetone, react at 45-55°C for 0.8-1.2 hours, cool to 40°C, add 1.5-2.5 parts of triethylamine and 140-160 parts of deionized water, stir at a rate of 2800-3200rpm for 25-35 minutes, and obtain nitrogen-phosphorus modified isocyanate polyurethane after reduced pressure distillation.

3. The corrugated paper according to claim 2, characterized in that: The preparation method of the modified montmorillonite is: A1. Mix 8-12 parts of montmorillonite and 90-110 parts of anhydrous toluene, perform ultrasonic treatment for 20-40 min under nitrogen protection, add 4-6 parts of polysiloxane, react at 105-115°C for 5-7 h, cool to 25°C, centrifuge, wash alternately with toluene and anhydrous ethanol 2-4 times, and vacuum dry at 70-90°C for 10-14 hours to obtain intermediate 1; A2, 95-105 parts of anhydrous N, N-dimethylformamide and 7-8 parts of cyanuric chloride were mixed, 2.5-3.5 parts of sodium carbonate and 45-55 parts of deionized water were added under ice bath conditions, stirred for 20-40 minutes, 4-6 parts of sodium alginate were added, reacted at 20-30°C for 3-5 hours, heated to 55-65°C, reacted for 1.5-2.5 hours, cooled, precipitated with acetone, washed 2-4 times, and vacuum dried at 45-55°C for 18-30 hours to obtain intermediate 2; A3. Mix 4-6 parts of intermediate 1, 2-4 parts of intermediate 2 and 900-110 parts of anhydrous N,N-dimethylformamide, ultrasonicate for 20-40 minutes, add 0.4-0.6 parts of triethylamine, react at 65-75°C for 7-9 hours under nitrogen protection, cool to 25°C, centrifuge, wash alternately with anhydrous N,N-dimethylformamide and acetone 2-4 times, and vacuum dry at 55-65°C for 18-30 hours to obtain modified montmorillonite.

4. The corrugated paper according to claim 3, characterized in that: The montmorillonite is sodium montmorillonite with a mesh size of 100 meshes.

5. The corrugated paper according to claim 3, characterized in that: The preparation method of the novel polysiloxane is: 90-110 parts of tetraethoxysilane, 25-35 parts of methyltrimethoxysilane, 20-30 parts of vinyltrimethoxysilane, 30-40 parts of phenyltrimethoxysilane and 200-250 parts of anhydrous ethanol are mixed to form a reaction system, and the reaction system is stirred uniformly under nitrogen protection, 2-3 parts of concentrated hydrochloric acid and 35-45 parts of deionized water are mixed to form an acid solution, and the acid solution is added to the reaction system under ice bath conditions of 0-5°C, and the temperature is raised to 2 0-30℃, stir for 1.5-2.5h, add 0.5-1.0 parts of triethylamine to adjust the pH to 6.5-7.5, heat to 55-65℃, react for 5-7h, reflux at 75-80℃ for 10-14h, cool and distill under reduced pressure, dissolve the product in tetrahydrofuran, filter through 0.45μm filter membrane, wash with n-hexane 2-4 times, centrifuge and vacuum dry at 45-55℃ for 36-60h to obtain polysiloxane.

6. The corrugated paper according to claim 1, characterized in that: The preparation method of the V-shaped flame retardant core base layer is as follows: 25-35 parts of waste paper pulp, 6-8 parts of boron carbide fiber, 2-5 parts of phosphorus nitrogen modified isocyanate polyurethane, and 10-20 parts of oxidized cassava starch are mixed, and after dehydration and molding, a V-shaped structure is formed by corrugated rollers.

7. The corrugated paper according to claim 1, characterized in that: The raw materials for preparing the upper paper / lower paper include: 100 parts of lemon eucalyptus powder, 20-30 parts of oxidized cassava starch, 35-45 parts of waste paper pulp, 10-12 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 7-10 parts of expanded graphite.

8. The corrugated paper according to claim 1, characterized in that: The preparation method of the upper paper / lower paper comprises the following steps: adding 100 parts of lemon eucalyptus powder, 20-30 parts of oxidized cassava starch, 35-45 parts of waste paper pulp, 100-12 parts of phosphorus-nitrogen modified isocyanate-based polyurethane, and 7-10 parts of expanded graphite into a pulping machine, adding water and stirring evenly to form slurry, performing a pulping treatment, forming sheets of the pulp after pulping, and hot pressing at 170-210° C. to obtain the upper paper / lower paper.

9. The corrugated paper according to claim 1, characterized in that: The preparation method of phosphonated urea-formaldehyde resin is as follows: B1. Mix 100-140 parts of a formaldehyde solution with a mass fraction of 35% to 40% and 80-120 parts of urea, react at 70°C for 1 hour, add 250-350 parts of diammonium phosphate and 4-6 parts of triethanolamine, heat to 80-90°C, react for 1.5-2.5 hours, and obtain a phosphated urea-formaldehyde prepolymer; B2. Mix 100 parts of phosphated urea-formaldehyde prepolymer with 20 parts of melamine at 60°C, add 0.5 parts of catalyst, heat to 90°C, react for 1.5-2h, and cool to 25°C to obtain phosphated urea-formaldehyde resin.

10. A method for preparing the environmentally friendly flame-retardant corrugated paper according to any one of claims 1 to 9, characterized in that: The preparation method comprises: coating the prepared flame retardant adhesive on the surface of the upper paper and the lower paper respectively, pressing and bonding the upper paper, the V-shaped corrugated core base and the lower paper in sequence, and drying them at room temperature to obtain environmentally friendly flame retardant corrugated paper; Wherein, the coating amount of the adhesive is 23-27g / m 2 .

Citation Information

Cited By

  • Composite paperboard with flame retardance and buffering performance

    CN121428880A

  • Composite paperboard having flame retardant and cushioning properties

    CN121428880B